Alkali Metal Chlorides Based Hydrogel as Eco‐Friendly Neutral Electrolyte for Bendable Solid‐State Capacitor. Issue 10 (12th March 2018) - Li, Hu; Wang, Xinxin; Jiang, Wen; Fu, Haoyu; Liang, Xiaoqiang; Zhang, Ke; Li, Zhe; Zhao, Chaochao; Feng, Hongqing; Nie, Jia; Liu, Ruping; Zhou, Gang; et al.
Abstract: Hydration greatly affects ionic state in an aqueous environment and thus influences their electrochemical performance. In this study, three alkali metal chlorides dissolved in neutral polyvinyl alcohol hydrogel are fully investigated for bendable solid‐state TiO2 nanotube capacitor (BSTC). Radius difference between bare ions and hydrated ions results in their obviously different electrochemical performance. Hydration makes lithium‐ion (Li + ) possess the largest hydrated radius and the lowest mobility, which endows it the best capacitance performance in BSTC by electrochemical characterization. BSTC with hydrated Li + achieves high capacitance retention rates of 87% at 1 V for 3000 cycles and of 70% at 2 V for 2500 cycles. Additionally, it has no significant capacitance variation when stored for one month or bended to 120°. Abstract : Alkali metal chlorides based poly(vinyl alcohol) (PVA) hydrogel as neutral electrolytes are fully investigated for bendable solid‐state capacitor. Hydration greatly affects ionic state in an aqueous environment and thus influences their electrochemical performance. Lithium chloride (LiCl) achieved the best capacitive behavior for the largest hydrated radius and lowest migration rate of Li + in PVA hydrogel.